Substitusi Rumput Lapangan dengan Kulit Buah Coklat Amoniasi dalam Ransum Domba Lokal - M Zain (Media Peternakan, 2009)
An experiment was aimed to evaluate the effect of substitution of native grass with ammoniated cocoa pod on digestibility and live weight gain of sheep. Three treatments were arranged in a randomized block design consisting of five replicates. The total of 15 head of 8-14 months old lokal sheeps with initial live weight 9-12 kg were used. The treatments were A= 50% native grass and 50% concentrate, B= 25% native grass+ 25% ammoniated cocoa pod + 50% concentrate C= 50% ammoniated cocoa pod + 50% concentrate. The results indicated that substitution of native grass with ammoniated cocoa pod did not significantly influence feed intake, digestibility, live weight gain and diet efficiency. It was indicated that ammoniated cocoa pod can be used to replace the native grass in sheep diet. Key words: cocoa pod, ammoniated, sheep, gain